Anti-social elements in Telugu drama serials – A study on Godavari District’s women - Savithri, K. Satya (International Journal of English Literature and Social Sciences (IJELS), 2019)
Women are like a fortress to the culture of India. These women, who are supposed to be the protectors of the wealth of Indian culture, it is the women, who gave birth to great people that earned fame across the world. It is the women, who struggled a lot to lead her life with virtues. 21st century woman proved herself in all the fields. She maintains a home and manages an office. She is the very embodiment of love, care, honesty and chastity. This is the greatness of a woman. But the portrayal of woman in daily serials is quite different. Daily soap operas are showing women as a symbol of cruelty, selfishness and as an anti-social personality. Many studies revealed the impact of the serials but my attempt through this study analyses how women were portrayed in Telugu daily serials and the perception of the women especially who are living in Godavari districts.